ART BUILDING IN BANDUNG - Marwoto (Jurnal Scientia, 2022)
The Art Building is a place or place to perform art performances, both traditional and modern, as well as a place to fulfill the community's need for art. The Art Building in Bandung is a facility or container that is considered important to support artistic activities in Bandung. The location around this project is an educational area, therefore, this Art Building will be very helpful in art learning activities. The purpose of this design is to provide an understanding of the Art Building which is designed with the theme of Regionalism Architecture. Architecture Regionalism in architecture is a movement in architecture that advocates the appearance of buildings which are the result of a compound of internationalism with modern cultural and technological patterns with roots, values and nuances of tradition that are still embraced by the local community. Regionalism (regionalism) emphasizes the disclosure of the characteristics of an area/place in contemporary architecture. This approach is one of the criticisms of Modern Architecture which views architecture as basically universal. The application of the theme of Regionalism Architecture to the Gedung Kesenian Bandung, is an architectural style designed